THE VILLAGE EDUCATION PROBLEM IN UKRAINE AND THE PRECARPATHIAN REGION VILLAGE SCHOOLS DEVELOPMENT PERSPECTIVES - Іванюк, Наталія Іванівна; Сав’юк, Лариса Олександрівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The Ukrainian village education quality modern situation analysis is presented, the education village infrastructure functioning problems are discussed, the propositions to overcome the difficult situation in the village education are given.